2018
DOI: 10.1111/1365-2478.12675
|View full text |Cite
|
Sign up to set email alerts
|

3D upper crustal density structure of the Deccan Syneclise, Central India

Abstract: A constrained 3D density model of the upper crust along a part of the Deccan Syneclise is carried out based on the complete Bouguer anomaly data. Spectral analysis of the complete Bouguer gravity anomaly map of the study region suggests two major sources: short wavelength anomalies (<100 km) caused primarily due to the density inhomogeneities at shallow crustal level and long wavelength anomalies (>100 km) produced due to the sources deeper than the upper crust. A residual map of the short wavelength anomalies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Analogously, Patro and Sarma (2016); Prasad et al. (2018) find that using higher‐resolution datasets, the magma bodies in Narmada‐Tapi Rift Zone are smaller and connected (if at all) thorough narrow zones instead of a larger, thicker, single magma body proposed originally by Bhattacharji et al. (2004).…”
Section: Deccan Traps Intrusive Structure–geophysical Observationsmentioning
confidence: 71%
See 2 more Smart Citations
“…Analogously, Patro and Sarma (2016); Prasad et al. (2018) find that using higher‐resolution datasets, the magma bodies in Narmada‐Tapi Rift Zone are smaller and connected (if at all) thorough narrow zones instead of a larger, thicker, single magma body proposed originally by Bhattacharji et al. (2004).…”
Section: Deccan Traps Intrusive Structure–geophysical Observationsmentioning
confidence: 71%
“…However, Rao et al (2018) used gravity datasets in combination with constraints from seismic observations, as well as magnetic datasets, and found that the observation can be better explained with much smaller crustal magma bodies along with a Moho depth underplate. Analogously, Patro and Sarma (2016); Prasad et al (2018) find that using higher-resolution datasets, the magma bodies in Narmada-Tapi Rift Zone are smaller and connected (if at all) thorough narrow zones instead of a larger, thicker, single magma body proposed originally by Bhattacharji et al (2004). 1).…”
Section: Upper Crustal Intrusive Bodiesmentioning
confidence: 73%
See 1 more Smart Citation
“…However, these long lifespans are only valid for upper‐crustal and felsic magmatic systems (e.g., Cooper, 2019; Mutch et al., 2019) in contrast to the tholeiitic basaltic composition of the Poladpur to Mahabaleshwar lavas. In addition, there is no geophysical evidence for large continuous upper crustal intrusive bodies below India, which could represent former magma reservoirs with corresponding dimensions (Mittal et al., 2021; Prasad et al., 2018). The detected intrusions are prismatic in shape and have a diameter between 5 and 15 km as well as a thickness of few km (e.g., Prasad et al., 2018), which is contrary to a single large upper crustal magma reservoir with volumes between 10 5 and 10 6 km 3 (Mittal & Richards, 2021; Mittal et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous geophysical experiments have been performed over the DVP to investigate its crustal structure. None of them, however, show evidence of an upper-crustal magma chamber beneath it (e.g., Bhattacharji et al, 2004;Chopra et al, 2014;Kaila et al, 1981;Krishna et al, 1991;Mohan & Kumar, 2004;Patro & Sarma, 2016;Patro et al, 2018;Prasad et al, 2018;Tiwari et al, 2001). Some of these studies do indicate the presence of magma underplating, albeit with poorly quantified thickness, location, velocity, and density.…”
Section: Introductionmentioning
confidence: 99%